EU firearms policies: general profiles (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
The European Union has developed a foreign policy on arms, to tackle the accumulation of small arms and light weapons in third countries and prevent it. The policy has been outlined by a 2005 Strategy and has been implemented over the years by an array of actions, taken at the international, regional, bilateral or national level. The aim of this paper is to sketch these actions, in order to offer a better understanding of this policy and of its implementation.Keywords: European Union, arms trade, international law, proliferation, small arms and light weapons